Exploring Karst Area Management for State Revenue Generation in the Aru Islands, Maluku Province - Ademiar; Anderson Basri (IHSA Institute, 2024)
This research explores the potential for karst area management to generate state revenue in the Aru Islands, Maluku Province, Indonesia. Karst landscapes, characterized by limestone formations, caves, and underground rivers, are integral to the ecological, socio-economic, and cultural fabric of the region. However, challenges such as unsustainable resource exploitation, environmental degradation, and governance gaps threaten the long-term sustainability of karst ecosystems and the well-being of local communities. Through a multi-disciplinary approach integrating ecological surveys, socio-economic analyses, and stakeholder consultations, this study assesses the ecological value of karst landscapes, identifies socio-economic opportunities and challenges, and proposes policy recommendations for sustainable development and revenue generation. Key findings underscore the ecological significance of karst areas, the importance of community engagement, and the need for strengthened governance mechanisms to promote inclusive growth, environmental conservation, and social equity in the Aru Islands. The research contributes to the growing body of knowledge on karst area management and provides actionable insights for policymakers, government agencies, civil society organizations, and local communities striving to achieve sustainable development goals in karst regions.